Iron Chelation and Iron Reducing Activity of Tissue Cultured and Tissue Culture Derived Mentha Spp. - Akash Deep, Pooja Rana, Giridhar Soni (Journal of Applied Pharmaceutical Science, 2017)
The present study was carried out to study the effect of maturity of tissue cultured and tissue cultured derived Mentha spp on iron chelation and iron reducing potential. Mentha sps. selected for the study were Mentha piperita (PPR 611), Mentha arvensis (SH) and Mentha spicata (SPR-8). Methanolic extracts of selected Mentha spp were prepared and total phenolic and flavonoid contents were determined in tissue cultured (TC) and tissue culture derived plantlets (TCo and TC1). Furthermore, a comparison of chelation of ferrous ions and iron reducing power of extracts was made in the three species. Total phenol content increased in time dependent manner and was found to be more in tissue culture derived plantlets (TC0and TC1) in all the three species compared to tissue cultured plants (TC). The phenols were found to be highest in SPR- 8 plants followed by PPR 611.On the contrary, flavonoid content decreased over growth period in all Mentha spp. Also PPR 611 showed higher content of flavonoids compared to other species. The difference in production of these secondary metabolites may be due to culture induced variations in biosynthetic pathways. The iron reducing potential of tissue culture derived plants also increased with increase in development period and SPR-8 showed more promising results. Tissue cultured raised and tissue culture derived plantlets of SPR-8 had better iron chelation property and the activity decreased in tissue cultured derived plantlets with an increase in development period.
Keywords: Mentha, reducing power, tissue culture, iron chelation, development periods.